(untitled) (Research, Society and Development, 2020)
The objective of the present study was to determine the prevalence, epidemiological and socioeconomic profile and risk factors associated with HIV-1 infection in elderly patients diagnosed with HIV/AIDS in the state of Piauí, Brazil. A total of 805 individuals seen at the Central Laboratory of Public Health of Piauí were included. The subjects were classified into two groups: a group of individuals 18 to 59 years old and a group of those 60 years or older. These individuals were tested for HIV-1 infection (ELISA), which was monitored by TCD4+/CD8+ lymphocyte count (flow cytometry) and viral load quantification (branched DNA method), and for coinfections with HBV, HCV and HTLV-1/2 (ELISA and PCR). They also answered an epidemiological questionnaire on socio-demographic, epidemiological and clinical characteristics. The frequency of HIV-1 infection in elderly patients was 3.7% (30/805). The majority of patients were male (66.6%), had a primary school education level (90%), were married (40%) and had a family income of 1 to 4 times the minimum wage (63.3%). The main behavioral risk factors associated with these individuals included lack of condom use (100%) and a history of Sexual Transmitted Diseases – STI (53.3%), surgery (63.3%) or blood transfusion (40%). The elderly patients also had a higher frequency of HIV-HTLV-1/2 co-infection (13.3%). Identifying the main characteristics related to HIV infection in the elderly is important to show that these individuals are also susceptible to HIV-1 infection and must be made aware of risk behaviors.